Metode Percepatan Pembangunan Pasar Besar Ngawi Menggunakan Metode Half Slab - Julistyana Tistogondo; Imanullah Sandy Pratama; Diah Ayu Restuti Wulandari (Universitas Dr. Soetomo, 2024)
The Ngawi Big Market development project, located on Jl. Sultan Agung, Sidomulyo, Ketangi, Kec. Ngawi, Ngawi Regency, East Java 63211. In this development project, it is necessary to calculate the budget plan and the exact implementation time to find out how much money is needed and how to calculate the time for the construction of the project. For this final project using the half slab precast method on the plate and for other elements still using the conventional method. To plan costs, must determine the method of implementation and also know the duration of the work in advance. So, it is necessary to do the volume calculation first. Then find out the productivity value of each type of work. So to get the value of work duration obtained from the calculation of volume divided by productivity. The calculation of the productivity value is obtained from field surveys. The results of these calculations can be used as input to the Microsoft Project software application for preparing schedules for each job. In the final results of calculating the cost and time of implementation of this project, the cost and duration of plate work with Halfslab is Rp. 2,666,765,984 with a duration of work for 35 days.